GVS-12 attenuates non-alcoholic steatohepatitis by suppressing inflammatory responses via PPARγ/STAT3 signaling pathways. Issue 17 (26th March 2019) - Wang, Yuhui; Zhang, Xiyang; Yuan, Bo; Lu, Xi; Zheng, Dongxuan; Zhang, Kefeng; Zhong, Mingli; Xu, Xiaotian; Duan, Xiaoqun
Abstract : Non-alcoholic steatohepatitis (NASH), a type of fatty liver disease, is characterized by excessive inflammation and fat accumulation in the liver. Abstract : Non-alcoholic steatohepatitis (NASH), a type of fatty liver disease, is characterized by excessive inflammation and fat accumulation in the liver. Peroxisome proliferator-activated receptor γ (PPARγ) agonist rosiglitazone has great potential in protecting against the development of NASH. However, long-term usage of rosiglitazone probably leads to many adverse reactions. In this research, GVS-12 was designed and synthesized as a PPARγ agonist with high selectivity, evidenced by increasing the activity of the PPARγ reporter gene and promoting the mRNA expression of the PPARγ responsive gene cluster of differentiation 36 (CD36). It was noteworthy that GVS-12 could ameliorate dysfunction and lipid accumulation by down-regulating the mRNA expression of interleukin-1β (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) in the liver of high fat diet (HFD)-induced rats and palmitic acid (PA)-stimulated hepatocellular carcinoma G2 (HepG2) cells. Moreover, PPARγ siRNA (siPPARγ) markedly diminished GVS-12 induced the down-regulation of mRNA expression of IL-1β, IL-6 and TNF-α in PA-stimulated HepG2 cells. Additionally, GVS-12 could reduce the phosphorylation level of STAT3 and up-regulate the protein expression of a suppressor of cytokine signaling 3 (SOCS3), which could be reversed by siPPARγ. In detail, SOCS3 siRNA (siSOCS3) diminished the inhibitory effect of GVS-12 on the mRNA expression of IL-1β, IL-6 and TNF-α. In conclusion, GVS-12 suppressed the development of NASH by down-regulating the mRNA expression of IL-1β, IL-6 and TNF-α via PPARγ/STAT3 signaling pathways.